Outcomes of cochlear implantation in children with inner ear malformations - BATMAN, ABDULLAH ÇAĞLAR; ŞAHİN, AKIN; ÇİPRUT, AYŞE AYÇA; CESUR, SIDIKA (SPRINGER, 2019)
Purpose To evaluate the surgical experience and auditory functions and progress of speech development of cochlear implantation in malformed ears. Materials and methods Between November 1995 and July 2017, thirty-seven patients (26 females and 11 males; mean age: 138.275 +/- 96.24 months) with diverse anomalies of the inner ear were retrospectively examined for surgical and audiological results. Speech Intelligibility Rating (SIR), Categories of Auditory Perception (CAP), Pure Tone Average (PTA), Speech Intelligibility Rating (SRT), and Word Discrimination Score (WDS) were the audiological tests used to evaluate the efficacy of CI in the malformed inner ears. Results CSF gusher was experienced by six patients (three with LVA (large vestibular aqueduct), one with IP (incomplete partition) I, and two with both IP II Mondini malformations and LVA). Two patients had transient facial paresis after surgery. All patients fully recovered within 6 months. The postoperative PTA, SRT, and WDS test results showed significant differences between progressive and congenital sensorineural hearing loss (p values < 0.05 for all). On the other hand, the postoperative CAP and SIR test results revealed no significant differences between the two groups. According to etiology, the PTA and SRT values were significantly lower in common cavity patients than the LVA patients (p values < 0.01); no significant differences were found among the other etiological groups. Conclusions Cochlear implantation is safe in children with inner ear malformations. However, the success rate is low compared to patients with normal anatomy in terms of audiological results; the most successful group of patients with inner ear malformation is large vestibular aqueduct.
Keywords: Cochlear implantation; Congenital inner ear anomaly; Sensorineural hearing loss; Auditory performance; Speech development; SPEECH-PERCEPTION; MASTOIDECTOMY